Educação continuada de professores de língua portuguesa: em busca de subsídios para uma proposta de formação centrada na escola - Arbolea, Tânia Aparecida (2009)
The subject continued formation of teachers of Portuguese Language elapsed of experiences in a professional passage of years of work as formadora, becoming possible to verify that the continued education already if placed as a process of permanent education for the professional development in face of the speed of information that modifies the educational field. With the objectives to know and to make a reflexiva reading on proposals developed in Portugal; to retake for a reading retrospect, projects developed in the PUC-SP, from proposals of the Secretariat of the Education of the State of São Paulo; e to search in the models subsidies for a proposal of continued action; the research searched basement in referring bibliographical research to the continued education of professors, mainly, in studious as Shön (1992), Nóvoa (1991, 1992) and Alarcão (1991, 1998), prioritizing the reflection in the action. For the aspects of the Literal Linguística, the theoretical support is based on Adam (2008), Beaugrande (1997), Koch (2006) and Fávero and Koch (2002), in virtue of approaches come back toward the concept of text, the textualidade and its principles. Also in them we are valid Serafini (2001) and Pear tree (2000, 2001ª, 2001b and 2002), a time that its works in offer endorsement to them regarding the education of the literal production under the optics of the process. The hypothesis of that the knowledge of projects implemented in the two countries and the reflection on its parameters would allow to elaborate subsidies for proposals of a continued formation of professors of centered Portuguese Language in the school was confirmed, still partially, a time that the research if abided only by the education of the literal production. In synthesis, it is concluded that the formation centered in the school is capable to make possible the professor to reflect on practical its for the resolution of problems, stimulating it the personal and professional development